2012
DOI: 10.6004/jnccn.2012.0073
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Adenocarcinoma, Version 2.2012

Abstract: The NCCN Clinical Practice Guidelines in Oncology (NCCN Guidelines) for Pancreatic Adenocarcinoma discuss the workup and management of tumors of the exocrine pancreas. These NCCN Guidelines Insights provide a summary and explanation of major changes to the 2012 NCCN Guidelines for Pancreatic Adenocarcinoma. The panel made 3 significant updates to the guidelines: 1) more detail was added regarding multiphase CT techniques for diagnosis and staging of pancreatic cancer, and pancreas protocol MRI was added as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
177
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(179 citation statements)
references
References 41 publications
2
177
0
Order By: Relevance
“…Endoscopic ultrasound (EUS) can complement other imaging modalities with valuable staging information and is good in detecting especially smaller lesions. At present, the routine use of endoscopic retrograde cholangiopancreatography or fluorine-18 fluorodeoxyglucose positron emission tomography cannot be recommended [8,13]. …”
Section: Diagnosticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Endoscopic ultrasound (EUS) can complement other imaging modalities with valuable staging information and is good in detecting especially smaller lesions. At present, the routine use of endoscopic retrograde cholangiopancreatography or fluorine-18 fluorodeoxyglucose positron emission tomography cannot be recommended [8,13]. …”
Section: Diagnosticsmentioning
confidence: 99%
“…In most cases, tumor diagnosis and resectability is adequately evaluable using one cross-sectional imaging study and the current state-of-the-art imaging modality is contrast-enhanced multidetector computed tomography (CT) with advanced volumetric processing techniques [8,13]. Patients are typically scanned in an arterial and venous phase.…”
Section: Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…About 80% of pancreatic carcinomas are located in pancreas head, and adenocarcinomas comprise 75% of them [1]. Strong evidence from previous studies showed that complete resection is the only chance for cure, which is possible only in 10% -20% of patients [2]. Thus, palliative managements are the sole treatment options for about 80% of pancreatic cancer patients.…”
Section: Introductionmentioning
confidence: 99%